A POLITICAL ECOLOGY OF THE CHIPKO MOVEMENT - Sya Kedzior (University of Kentucky, 2006)
The Indian Chipko movement is analyzed as a case study employing a geographically-informed political ecology approach. Political ecology as a framework for the study of environmental movements provides insight into the complex issues surrounding the structure of Indian society, with particular attention to its ecological and political dimensions. This framework, with its focus on social structure and ecology, is distinct from the more "traditional" approaches to the study of social movements, which tend to essentialize their purpose and membership, often by focusing on a single dimension of the movement and its context. Using Chipko as a case-study, the author demonstrates how a geographical approach to political ecology avoids some of this essentialization by encouraging a holistic analysis of environmental movements that is characterized by a "bottom-up" analysis, grounded at the local level, which also considers the wider context of the movement's growth by synthesizing socio-political and ecological analyses. Also explored are questions on the importance of ender-informed approaches to the study of environmental activism and participation in environmental movements in India